Risk of Malignant Neoplasms of Kidney and Bladder in a Cohort Study of the Diabetic Population in Taiwan With Age, Sex, and Geographic Area Stratifications. Issue 38 (September 2015) - Chen, Hua-Fen; Chen, Shwe-Winn; Chang, Ya-Hui; Li, Chung-Yi; Gao., Chun
<x xml:space="preserve">Abstract</x> Abstract Diabetes has been reported to increase the risk of malignant neoplasms of kidney and bladder, but the studies' results are still inconclusive. Age, sex, and geographical area-specific incidence and relative risks of above neoplasms are also scarce in the literature. We prospectively investigated the age, sex, geographical area-specific incidence and relative risks of kidney and bladder neoplasms in diabetic population of Taiwan. Diabetic patients (n = 615, 532) and age- and sex-matched controls (n = 614, 871) were linked to inpatient claims (2000–2008) to identify the admissions for malignant neoplasm of kidney (International Classification of Diagnosis, 9th version, Clinical Modification: 189) and bladder (International Classification of Diagnosis, 9th version, Clinical Modification: 188). The person-year approach with Poisson assumption was used to evaluate the incidence density. We also estimated the age, sex, and geographical area-specific relative risks of above malignancy in relation to diabetes with Cox proportional hazard regression model. The overall incidence density of malignant neoplasm of kidney for diabetic men and women were 3.87 and 4.28 per 10, 000 patient-years, respectively; the corresponding figures for malignant neoplasm of bladder were 5.73 and 3.25 per 10, 000 patient-years. Compared with the controls, diabetic men were at significantly increased hazards of kidney (covariate adjusted hazard ratio [aHR]: 1.31, 95% confidence interval [CI] 1.18–1.46) and bladder aHR: 1.13, 95% CI 1.04–1.23). Diabetic women, on the contrary, only experienced significantly elevated hazard of kidney neoplasm (aHR: 1.14, 95% CI 1.04–1.26). Diabetic men aged >65 years showed the most significantly increased hazard of developing neoplasm of kidney (aHR: 1.40) and bladder (aHR: 1.13). The most significantly increased hazard of kidney neoplasm was noted for women diabetic patients aged >65 years. There was also a significant interactive effect of geographic area with diabetes on the incidence of kidney and bladder neoplasms in both sexes. Diabetic men >45 years and diabetic women >65 years were found to have significantly increased hazard of malignant neoplasm of kidney, but only diabetic men >65 years were at significantly increased hazard of bladder neoplasm. The significant geographic variations in incidence and relative hazard of kidney and bladder neoplasms warrant further investigations of the underlying reasons.